2019
DOI: 10.1155/2019/4123154
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis spp. in Romanian Slaughtered Cattle: Molecular Characterization and Epidemiological Significance of the Findings

Abstract: Species of the genus Sarcocystis are recognized as protozoan parasites infecting a wide range of animals, including humans. This study aimed to provide data on the occurrence, genetic characterization, and epidemiological significance of Sarcocystis spp. in cattle destined for human consumption in Romania. A total of 117 heart samples from slaughtered cattle in three southwestern Romanian counties (Dolj, Timiș, and Gorj) were analyzed in order to detect sarcocysts, using fresh examination microscopic technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Sarcocystis was also detected in cattle heart at prevalence rates of 100% and 17.9% from Brazil and Romania by Ferreira et al [36] and Imre et al [37], respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Sarcocystis was also detected in cattle heart at prevalence rates of 100% and 17.9% from Brazil and Romania by Ferreira et al [36] and Imre et al [37], respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, several trends in the prevalence of Sarcocystis species can be indicated. Most studies carried out in cattle reported the highest prevalence of S. cruzi employing canids as definitive hosts [10,14,15,18,37,[40][41][42][43][44]. By contrast, a relatively low prevalence of S. hirsuta using felids as definitive hosts was often recorded [14,15,37,41,45].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies carried out in cattle reported the highest prevalence of S . cruzi employing canids as definitive hosts [ 10 , 14 , 15 , 18 , 37 , 40 44 ]. By contrast, a relatively low prevalence of S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitive hosts of these species are canids (S. cruzi), felids (S. hirsuta, S. bovini, S. bovifelis and S. rommeli) and humans (S. hominis and S. heydorni). It has been found that among these species S. hominis and S. heydorni caused zoonotic infections, infected humans with infected pork and beef or contaminated food, and calves were infected with sporocysts excreted in feces as a result of infection (6,10,15,18).…”
Section: Introductionmentioning
confidence: 99%